A global country‐level analysis of the relationship between obesity and COVID‐19 cases and mortality. Issue 12 (25th August 2021) - Foo, Oliver; Hiu, Shaun; Teare, Dawn; Syed, Akheel A.; Razvi, Salman
Abstract: Aim: To assess the association of country‐level obesity prevalence with COVID‐19 case and mortality rates, to evaluate the impact of obesity prevalence on worldwide variation. Methods: Data on COVID‐19 prevalence and mortality, country‐specific governmental actions, socioeconomic, demographic, and healthcare capacity factors were extracted from publicly available sources. Multivariable negative binomial regression was used to assess the independent association of obesity with COVID‐19 case and mortality rates. Results: Across 168 countries for which data were available, higher obesity prevalence was associated with increased COVID‐19 mortality and prevalence rates. For every 1% increase in obesity prevalence, the mortality rate was increased by 8.3% (incidence rate ratio [IRR] 1.083, 95% confidence interval [CI] 1.048‐1.119; P  < 0.001) and the case rate was higher by 6.6% (IRR 1.066, 95% CI 1.035‐1.099; P  < 0.001). Additionally, higher median population age, greater female ratio, higher Human Development Index (HDI), lower population density, and lower hospital bed availability were all significantly associated with higher COVID‐19 mortality rate. In addition, stricter governmental actions, higher HDI and lower mean annual temperature were significantly associated with higher COVID‐19 case rate. Conclusion: These findings demonstrate that obesity prevalence is a significant and potentially modifiable risk factor of increased COVID‐19 national caseload and mortality. Future research to study whether weight loss improves COVID‐19 outcomes is urgently required.